2000
DOI: 10.7748/ns2000.10.15.6.35.c2933
|View full text |Cite
|
Sign up to set email alerts
|

The nurse lecturer’s role in mentoring the mentors

Abstract: Respondents indicated that they wished to see lecturers visiting the practice placement areas and providing support, particularly in relation to assessment of students. Also highlighted in this study is the need for more effective communication between placement areas and academic staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…Preceptors have reported a desire to receive feedback from CNMs on how effective they are with undertaking this role (Allen & Simpson 2000, McCarthy 2006). Researchers agree, and suggest that feedback for preceptors should take the form of clarifying expectations, and, providing feedback on their performance in the role (Atkins & Williams 1995, Duffy et al. 2000).…”
Section: Organizational Supportmentioning
confidence: 99%
“…Preceptors have reported a desire to receive feedback from CNMs on how effective they are with undertaking this role (Allen & Simpson 2000, McCarthy 2006). Researchers agree, and suggest that feedback for preceptors should take the form of clarifying expectations, and, providing feedback on their performance in the role (Atkins & Williams 1995, Duffy et al. 2000).…”
Section: Organizational Supportmentioning
confidence: 99%
“…A key factor is that they are often poorly prepared before taking on the role (Yonge et al, 2002;Paton and Binding, 2009;Hamshire et al, 2012). Insufficient training and preparation for mentors is problematic for maintaining high standards of supervision in practice (Duffy et al, 2000;Hamshire et al, 2012). 'Learning guides' are commonly asked to take on these roles, selected due to their clinical experience and abilities rather than their education preparation or ability to facilitate learning (Paton and Binding, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate training and preparation for mentors has previously been highlighted as a major barrier to supporting students to apply their knowledge appropriately and develop capability (Duffy et al, 2000;Henderson and Eaton, 2013) The training officers and academics in the study were very committed to the programme and demonstrated a keen interest in supporting improvements, but limited 'transactional dialogue' (Brookfield,1986, p.20) was evident. Transactional dialogue ensures that each group understands each other's workplace culture and dominant language with a sharing of viewpoints and interpretations to develop a real partnership.…”
Section: Findings and Discussionmentioning
confidence: 99%